Silicon isotope homogeneity in the mantle - Savage, P; Georg, R; Armytage, R; Williams, H; Halliday, A (Elsevier, 2010)
Thirty-five mafic and ultramafic rocks have been analysed for their silicon isotopic composition to very high precision with the aim of providing a robust average value for the silicate earth. This is of importance to studies using the difference between meteorite and terrestrial isotope composition to quantify silicon sequestration during core formation and, also, for understanding crustal processes. The δ³⁰Si values of the samples are more limited than previously reported, ranging between just -0.39 and -0.23‰ despite significant variations in chemical and other isotopic compositions. A hint of a trend exists between δ³⁰Si and both SiO₂ and Al₂O₃, which can be explained by concentration of the heavier isotopes in the melt as a function of silica polymerisation. Our best estimate for the δ³⁰Si of the bulk silicate earth (BSE) is -0.29 ± 0.08‰ (2 s.d.).